2005
DOI: 10.1074/jbc.m502929200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Dentin Sialophosphoprotein Expression by Runx2 during Odontoblast Cytodifferentiation

Abstract: Dentin sialophosphoprotein (DSPP) consists of dentin sialoprotein (DSP) and dentin phosphoprotein (DPP). The spatial-temporal expression of DSPP is largely restricted during differentiational stages of dental cells. DSPP plays a vital role in tooth development. It is known that an osteoblast-specific transcription factor, Runx2, is essential for osteoblast differentiation. However, effects of Runx2 on DSPP transcription remain unknown. Here, we studied different roles of Runx2 in controlling DSPP expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
140
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(154 citation statements)
references
References 73 publications
8
140
1
3
Order By: Relevance
“…These observations suggest that the expression of the specific gene DSPP during dentinogenesis is governed not only by differentially expressed transcription factors and growth factors (61,(66)(67)(68)(69)(70), but also by differentially expressed miRNAs.…”
Section: Discussionmentioning
confidence: 93%
“…These observations suggest that the expression of the specific gene DSPP during dentinogenesis is governed not only by differentially expressed transcription factors and growth factors (61,(66)(67)(68)(69)(70), but also by differentially expressed miRNAs.…”
Section: Discussionmentioning
confidence: 93%
“…Bone morphogenetic protein/TGF␤ stimulation triggers expression of RUNX2 and its target genes in osteoblasts. However, the same response in odontoblasts is triggered by fibroblast growth factor family of proteins (28). Therefore, it was necessary to study the involvement of GRP-78 in the endocytosis of DMP1 in osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, BMP2 is involved in specifying the fate of the dental mesenchymal cells. DSPP expression was observed in odontoblasts at the bell stage and continuously through later stages in mouse teeth by in situ hybridization assay (4,5,7). Compared with other tissues such as bone, DSPP is highly expressed in odontoblasts, suggesting its important biological functions during odontogenesis.…”
mentioning
confidence: 96%
“…Recently, it has reported that DSPP extracted from porcine teeth consists of three dentin matrix proteins as follows: DSP, DPP, and dentin glycoprotein, which is located between DSP and DPP domains (14). DSPP is expressed predominantly in odontoblasts and transiently in preameloblasts (4,5). Heterogeneous mutations of human DSPP are associated with dentinogenesis imperfecta type II (DGI-II), type III (DGI-III), and dentin dysplasia type II (DD-II) (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation